2011
DOI: 10.1152/ajpheart.01008.2010
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise training provides left ventricular tolerance to acute pressure overload

Abstract: The present study evaluated the impact of moderate exercise training on the cardiac tolerance to acute pressure overload. Male Wistar rats were randomly submitted to exercise training or sedentary lifestyle for 14 wk. At the end of this period, the animals were anaesthetized, mechanically ventilated, and submitted to hemodynamic evaluation with biventricular tip pressure manometers. Acute pressure overload was induced by banding the descending aorta to induce a 60% increase of peak systolic left ventricular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Three assays were performed. This method is in accordance to Moreira-Gonçalves and collaborators with some modifications [25]. Three-dimensional surface plot analyses were generated with the “Surface Plot” function of Image J 1.44 (http://rsbweb.nih.gov/ij/download.html).…”
Section: Methodsmentioning
confidence: 99%
“…Three assays were performed. This method is in accordance to Moreira-Gonçalves and collaborators with some modifications [25]. Three-dimensional surface plot analyses were generated with the “Surface Plot” function of Image J 1.44 (http://rsbweb.nih.gov/ij/download.html).…”
Section: Methodsmentioning
confidence: 99%
“…Swim training is known to promote favorable cardiac outcomes including protection from various cardiac insults 17, 22, 23 . We have shown that when GRK5 is elevated in cardiac myocytes an early and progressive HF phenotype arises after TAC 4-6 .…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies in the literature have been performed in non-transgenic rodents to demonstrate the beneficial effects of exercise either prior to or after cardiac insult 22, 31-33 . Thus, we didn't study non-transgenic animals alone for swimming since our goal was to specifically address whether exercise in the face of cardiac-specific overexpression of GRK5 led to pathological changes and if swimming caused the nuclear localization of GRK5.…”
Section: Discussionmentioning
confidence: 99%
“…The slides were dewaxed in xylene and hydrated through graded alcohols finishing in PBS solution. Deparaffinized sections of lung tissue were stained for immunohistochemical staining of rabbit anti‐HMGB1 (1:400 dilution; Abcam, Cat# ab79823, RRID:AB_1603373), using the secondary anti‐body goat biotinylated anti‐rabbit (1:200 dilution; Vector Laboratories, Cat# BA‐1000, RRID:AB_2313606) and counterstained with hematoxylin‐eosin, as previously described (Moreira‐Goncalves et al, ).…”
Section: Methodsmentioning
confidence: 99%